Developing reading skills - Milan Spears, Deanne (McGraw Hill, 1995)
Designed for reading courses at the intermediate and advanced level.As in past editions, this text continues to feature a wide range of interesting and diverse selections as well as a comprehensive teaching apparatus. Using practice prose similar to the kind they will encounter in the classroom, students are encouraged to analyze, interpret, question, and even challenge the words of the writer.